(untitled) (Medicine Today, 2015)
Aim of this study is to educate pregnant women about posture and application of biomechanical principles in functional and work related activities and to prevent low back pain with help of Exercise Program and Education. Patients were randomly allocated in two groups. Group A included 30 patients and they received traditional antenatal care. Group B included more 30 patients and received therapeutic exercise and ADL instructions. They had one visit every two week for six weeks. In each visit both groups were evaluated for variables including pain, tenderness, mobility index and sleep. Pain was assessed by subjective intensity and VAS; tenderness was evaluated by tenderness index, mobility index by scoter test and SLR (straight leg rising). All the relevant collected data were recorded in prescribed data sheet and analyzed by using computer based statistical packages for social science (SPSS). A p value < 0.05 was considered as significant. Studentst test and Chi-square test was done to see the level of significance as required. The Study concluded that the back care in the form of Exercise Program and Postural Education given to women as early in their pregnancy as possible may prevent back pain or decrease the severity of back pain if it occurs. Medicine Today 2015 Vol.27(1): 8-11